PERSEPSI PNS GENERASI MILENIAL TERHADAP SISTEM PEMBELAJARAN DARING DI KABUPATEN PATI - NURUL DINIYATI (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2022)
This study aims to determine the perception of the millennial generation of civil servants towards the online learning system in Pati district. This study uses a qualitative approach with analytical descriptive methods through survey techniques. Based on the results of the study, it was found that there are at least three components that need adjustment in online learning, especially if the target participants are millennials, namely training strategy, facilitators and learning media. For training, it is necessary to have wider opportunities for participants to manage study time, study strategies and flexible assignment deadlines. For facilitators, it is necessary to have qualified competence in the field of training that is being taught, then be able to deliver it in an interesting, communicative and also important way, the facilitator must consider the participants as partners who are ready to help participants learn. Finally, the learning media provided must be varied, not monotonous, only on one learning source and of course the learning resources are arranged in an effective, attractive, accountable and accommodated participant's interest in the digital world or technology. Although it is necessary to adjust the three components, the education and training institution must still focus on the minimum achievement criteria for a training in accordance with the training institution goal. ABSTRAKPenelitian ini ertujuan untuk mengetahui persepsi PNS generasi milenial terhadap sistem pembelajaran daring di kabupaten Pati. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif analitis melalui teknik survei. Berdasarkan hasil penelitian ditemukan bahwa setidaknya ada tiga komponen yang perlu penyesuaian dalam pembelajaran online utamanya jika target pesertanya adalah kalangan milenial, yaitu strategi pelatihan, fasilitator dan media pembelajarannya. Untuk pelatihan secara perlu adanya kesempatan yang lebih luas bagi peserta untuk mengatur waktu belajar, strategi belajar dan deadline penugasan yang cukup fleksibel. Untuk fasilitator perlu kompetensi yang mumpuni dibidang mata pelatihan yang diampu, kemudian mampu menyampaiakan dengan cara yang menarik, komunikatif serta taak kalah penting fasilitator harus menganggap peserta sebagai mitra yang siap membantu belajar peserta. Terakhir media pembelajaran yang diberikan harus bervariasi, tidak monoton hanya pada satu sumber belajar dan tentunya sumber belajar tersebut disusun dengan efektif, menarik, dapat dipertanggung jawabkan dan mengakomodir ketertarikan peserta dengan dunia digital atau teknologi. Meski perlu penyesuaian pada tiga komponen tersebut, akan tetapi badan diklat harus tetap fokus pada kriteria ketercapaian minimal suatu pelatihan sesuai dengan yang ditetapkan badan diklat tersebut.